2019
DOI: 10.1681/asn.2018090901
|View full text |Cite
|
Sign up to set email alerts
|

IL-34–Dependent Intrarenal and Systemic Mechanisms Promote Lupus Nephritis in MRL-Faslpr Mice

Abstract: Background In people with SLE and in the MRL-Fas lpr lupus mouse model, macrophages and autoantibodies are central to lupus nephritis. IL-34 mediates macrophage survival and proliferation, is expressed by tubular epithelial cells (TECs), and binds to the cFMS receptor on macrophages and to a newly identified second receptor, PTPRZ. Methods To investigate whether IL-34-dependent intrarenal and systemic mechanisms promote lupus nephritis, we compared lupus nephritis and systemic illness in MRL-Fas lpr mice expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 54 publications
4
38
0
Order By: Relevance
“…It is expressed in several organs, including in tubular cells of the kidney 52 . IL34 supports the growth and survival of primary human monocytes and induces their differentiation into type 2 macrophages 53 IL34 has been linked with autoimmune and inflammatory diseases such as rheumatoid arthritis 53,54 , hepatitis C infection 55 , lupus nephritis 56 , inflammatory bowel disease 57 . It has been linked to chronic kidney injury and kidney graft rejection 52 , and to cancers including osteosarcoma 58 or lung cancer 59 .…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed in several organs, including in tubular cells of the kidney 52 . IL34 supports the growth and survival of primary human monocytes and induces their differentiation into type 2 macrophages 53 IL34 has been linked with autoimmune and inflammatory diseases such as rheumatoid arthritis 53,54 , hepatitis C infection 55 , lupus nephritis 56 , inflammatory bowel disease 57 . It has been linked to chronic kidney injury and kidney graft rejection 52 , and to cancers including osteosarcoma 58 or lung cancer 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Wada et al recently demonstrated robust RTEC expression of IL-34 in biopsies from LN patients and MRL-Fas lpr lupus mice, with significant associations between expression levels and disease activity. Further mechanistic investigations using this lupus mouse model showed that IL-34 enhances intrarenal macrophage accumulation/proliferation, leading to macrophage-mediated RTEC apoptosis ( 52 ). These findings identify IL-34 as a novel therapeutic target of RTEC-mediated immunopathogenesis in LN.…”
Section: Rtec Cytokine Production In Lnmentioning
confidence: 99%
“…However, as mentioned earlier, elevated levels of M-CSF are also observed in different pathologies. There are multiple publications linking M-CSF/IL-34 and CSF-1R signaling in models of arthritis ( 113 – 116 ), diabetes ( 117 ), systemic lupus erythematosus ( 85 , 118 ), cancer ( 119 121 ), amyotrophic lateral sclerosis ( 122 ), Parkinson's disease ( 123 ), and Alzheimer's disease ( 124 126 ). In an effort to determine the role of M-CSF/IL-34 and CSF-1R signaling in MS, different groups used potent c-fms tyrosine kinase inhibitors, which block M-CSF signaling.…”
Section: Targeting Myeloid Cell Activation and Cytokinesmentioning
confidence: 99%